P289 Best analgesia control in pancreatic adeno – carcinoma (the BAC-PAC study)- a prospective cohort study. (19th June 2022) - Koulouris, Andreas; Clark, Allan; Hart, Andrew; Alexandre, Leo
Abstract : Introduction: The standard care for the management of abdominal pain in patients with inoperable pancreatic cancer consists of opioids. Endoscopic Ultrasound-guided Coeliac Plexus Neurolysis (EUS-CPN) may be indicated if opioids are ineffective or poorly tolerated due to serious side effects. Limited and conflicting trial data is available on the efficacy of EUS-CPN, if administered early (soon after paom onset). This study aimed to assess the feasibility, justification and establish the design considerations of a randomised trial of early EUS-CPN versus standard care. These are determined by clinical parameters including fitness for endoscopy, survival after the pain onset and the standard error for possible outcome measures. Methods: This was a prospective observational study. Patients with inoperable pancreatic adenocarcinoma with an Eastern Co-operative Oncology Group (ECOG) performance status of 0-3 and expected survival of at least one month were eligible. Patients were asked to complete monthly questionnaires on their performance status, pain levels, analgesic use, quality of life (QoL) and healthcare resource use. Patient carers were also involved, completing questionnaires on their quality of life. Results: Over a total period of twelve months 143 patients were screened for eligibility, of which 56 met eligibility criteria. In total, 12 (21%) patients were recruited. Medical performance status ranged between 0 and 2 for those in pain. The median survival from the first record of pain was 5.2 (IQR 2.46-5.9) months. There were no statistically significant differences in the characteristics (age, sex, cancer stage) between participants and those who declined participation. The QoL of carers was moderately impaired at all time points (EQ-5D-5L summary index scores 0.86-0.89). In total, 80% of the questionnaires were completed and returned. The median Visual Analogue Score for pain was 2.6 (0.8-5.1) and the median daily morphine dose was 36 (20-48) mg. Discussion: Recruitment rates remained low throughout this study. Therefore, estimates of key outcomes were imprecise for: fitness for endoscopy at the time of the pain onset; survival time after the pain onset; time from diagnosis to first opioid prescription; and the descriptive statistics of the possible outcome measures of a future trial (pain scores, opioid doses and QoL scales). Despite these limitations, overall this study supports the justification of trial administering endoscopic analgesia. However, uncertainties remain with regards to its feasibility. In a future trial, data collection procedures should minimise burden to patients. Further observational research with sufficient sample size and follow-up is required to further inform the design and feasibility of a future trial of early EUS-CPN vs. standard care.